ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM MEMILIH OPERATOR SELULER (Studi pada Sebuah Perguruan Tinggi di Yogyakarta) (Fokus Ekonomi, 2008)
Based on this research, it’s found that many factors can influence the consumer decisionto choose cellular’s operator. This article explains about the influence of merk, price, quality andpromotion towards consumer decision to choose cellular’s operator. The sample of this researchare university students in Yogyakarta. The result of this research shown that quality andpromotion have significant effect to consumer decision to choose cellular’s operator.Key words : Consumer decision, cellular’s operator, quality, promotion